GREEN BUDGETING: SDGS-BASED BUDGETING PLANNING MODEL IN LABUAN VILLAGE - Panjili, Moh Yusran; Mustamin; Bakry, Moh Iqbal; Jurana (ISAFIR: Islamic Accounting and Finance Review, 2025)
Sustainable development is a global agenda that encourages the integration of environmental aspects in village budget planning. This study aims to develop a green budgeting model based on the Sustainable Development Goals (SDGs) in Labuan Village. The method used was descriptive qualitative research using interview techniques with five informants, consisting of community leaders and village officials. The results showed that although SDG principles have been adopted through programs such as BUMDes and TPS3R waste management, the integration of environmental aspects in village planning and budgeting is still limited. The main constraints include budget limitations and village officials' understanding of the concept of green budgeting. However, there are concrete efforts to include environmental considerations in the preparation of the APBDes and transparent reporting through the Village Information System (SID). The implications of this research indicate the importance of strengthening institutional capacity and community participation in supporting environmentally sound budget governance. The green budgeting model developed can serve as a reference for other villages in realizing inclusive and sustainable development.